The battles that made Abraham Lincoln : how Lincoln mastered his enemies to win the Civil War, free the slaves, and preserve the Union - Tagg, Larry (Savas Beatie, 2012)
A timely look at the atmosphere of political hostility surrounding the Civil War, and the venom faced by America's sixteenth president. Today, Abraham Lincoln is a beloved American icon, widely considered to be our best president. It was not always so. This book takes a look at what Lincoln's contemporaries actually thought and said about him during his lifetime, when political hostilities, and ultimately civil war, raged. The era in which our sixteenth president lived and governed was the most rough-and-tumble in the history of American politics. The hostility behind the criticism aimed at Lincoln by the great men of his time, on both sides of the Mason-Dixon line, is startling, the spectacular prejudice against him often shocking for its cruelty, intensity, and unrelenting vigor. The plain truth is that Lincoln was deeply reviled by many in his time. This book is both an entertaining read and a well-researched, serious look at the political context that begat the president's predicament. Lincoln's humanity has been unintentionally trivialized by some historians and writers who have hidden away the real man in a patina of bronze. This book helps us better understand the man he was, and how history is better and more clearly viewed through a long-distance lens. "Not the warm and fuzzy portrait we're used to seeing ... An eye-opening study, the first of its kind to focus on what Lincoln's contemporaries really thought of him. On the other hand, this is not mean-spirited Lincoln-bashing ... Tagg assesses his presidency through the social and political context of mid-19th century America. It was a time, for example, when 'the rabid press routinely destroyed the reputations of public men, ' when the stature of the presidency, 'stained by feeble performances from a string of the poorest presidents in the nation's history, ' had plunged over decades."--Civil War Times Magazine.